Integration and innovation: medical and health consortia improving continuing medical education in China - An, Kang; Zhang, Jinyi; Wang, Xingyou; She, Yi; Li, Shuangqing; Li, Sheyu (Frontiers in Public Health, 2025)
BackgroundPrimary health care (PHC) is the cornerstone of the healthcare system in China. The medical and health consortia (medical consortia) integrate resources of continuing medical education (CME) to bridge competency gaps among healthcare providers. This narrative review aims to explore the innovative models of CME within the framework of medical consortia.MethodsSearches were conducted in both Chinese and English databases to broaden the scope of the review, including China National Knowledge Infrastructure, Wanfang Data, and PubMed. Chinese policy documents were retrieved from official websites of China’s National Health Commission. The review analyzed existing policy documents (2010–2025) and relevant literature, supplemented by an institutional application example of the West China Hospital–Fangcao Community Health Service Center Medical Consortium to explore challenges and recommendations.ResultsChina developed a series of policies to promote the construction of medical consortia, with a focus on resource-sharing between tertiary and PHC institutions. A literature search yielded 196 articles, including qualitative studies, quantitative studies, and reviews, of which 48 met inclusion criteria in the review. Seven policy documents were included in the analysis. The synergy between medical consortia and CME brought benefits to both healthcare providers and the health system. Key innovations included clinical scenario-oriented training, remote consultation, and flexible training modalities. However, the reviewed literature highlighted persistent challenges, including regional disparities in resources, limited financial incentives for general practitioners (GPs), and a shortage of qualified trainers. Overcoming barriers such as regional resource disparities and improving the intrinsic motivation of GPs remained critical to the implementation of CME.ConclusionMedical consortia offer platforms for the delivery of CME, while CME supports the development of medical consortia. These innovations enhance collaboration between specialists and GPs, thereby optimizing patient referrals and follow-up care.